Personnel controlling instruments and their use in management of human resources in the company Fatra, a.s. - Bednaříková, Marie; Vávra, Jan; Filip, Tomáš (University of Pardubice, 2013)
At present, the objective of all companies is first of all reduction of the costs and the effective way of investments into the companies sections. However, the human resourses section belongs among these ones very rarely. Introduction of controlling in the personnel area can help the management of human resources not to be so overlooked and can help the company to reduce its one employee costs and to increase the employee’s productivity. Personnel controlling helps the management of company to get and to analyse the information in a form of reports necessary for its decisions and effective management. This paper deals with the problem issues of use of personnel controlling instruments in company, and it is accompanied by a research having taken place in early 2013 and being focused on the personnel controlling instruments and their use in the management of human resources in the company Fatra, a.s.